PERANCANGAN SISTEM INFORMASI EVALUASI PASCA PELATIHAN KESEHATAN DI KEMENTERIAN KESEHATAN - Ricaesar, Nopianto; Siregar, Kemal Nazaruddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The industrial revolution and the current era of information technology have touched various fields, including health. Competency development of health human resources is something that must be done to be able to adapt in the era of the industrial revolution 4.0. In an effort to develop the competence of Health Human Resources, training is a form that is commonly carried out today. Post-training evaluation is a form of training evaluation to determine the effectiveness of a training so that training can be continuously modified to achieve the best effectiveness. Evaluation of post-health training is currently still done manually, which causes not all health training to be evaluated because it requires a lot of resources and budget. The use of information technology in conducting post-training evaluations can be a solution to existing problems. The post-health training evaluation is carried out by developing an information system for the post-health training evaluation that can be carried out quickly, precisely and massively. The purpose of this research is to design an evaluation information system after health training to the system design stage. The development method uses the System Development Life Cyle (SDLC) with the waterfall model until the system design stage. System design is done by making context diagrams, ERD, TRD, Data Dictionary, Flow Chart and DFD. The design of this information system is expected to be the basis for the development of a more comprehensive health EPP information system in the future.